2012
DOI: 10.1111/j.1442-9071.2012.02845.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vascular endothelial growth factor upregulation on retinal gene expression in the Kimba mouse

Abstract: An early spike in vascular endothelial growth factor induced significant long-term retinal neovascularisation associated with changes to the retinal ganglion, photoreceptor and Müller cells. Overexpression of vascular endothelial growth factor led to dysregulation of photoreceptor metabolism through differential expression of Nr2e3, endothelin 2, betacellulin and semaphorin 3C. Alterations in the expression of these genes may therefore play key roles in the pathological mechanisms that result from retinal neov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…Lack of Edn2 upregulation thus accounts for the difference in endothelin protein content between WT and Esr2-Edn2KO mice at hCG12 hours. Multiple attempts at immunohistochemical localization of EDN2 using anti-EDN2 antibody (Abcam 197763) 55 did not produce specific staining results (Figure S2). IHC staining was similar between WT, global Edn2KO, and granulosa cell-specific Edn2KO tissues and did not match phenotypic defects observed in global Edn2KO mice (expiration at eight days of age).…”
Section: Resultsmentioning
confidence: 99%
“…Lack of Edn2 upregulation thus accounts for the difference in endothelin protein content between WT and Esr2-Edn2KO mice at hCG12 hours. Multiple attempts at immunohistochemical localization of EDN2 using anti-EDN2 antibody (Abcam 197763) 55 did not produce specific staining results (Figure S2). IHC staining was similar between WT, global Edn2KO, and granulosa cell-specific Edn2KO tissues and did not match phenotypic defects observed in global Edn2KO mice (expiration at eight days of age).…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Recently, we reported a reduction of VEGF gene expression in the retina of OXYS rats compared to the parent Wistar strain (control) during retinopathy progression 12 ; this effect may be linked to the early alterations in RPE cells and choroid vessels in OXYS rats. We supposed that such changes are prerequisite to the development of retinopathy and that their reversal is necessary for the prevention of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The heterozygous Akita male mice develop features similar to early pathophysiological changes of diabetic complications, but fail to exhibit the advanced stage vascular dysfunctions. The non-diabetic Kimba (trVEGF029) mouse model, in which photoreceptors transiently overexpress hVEGF, is characterized by several early and advanced DR-associated vascular changes such as vascular permeability, capillary non-perfusion, microaneurysms and retinal neovascularization [119,[122][123][124][125][126][127]. It has been reported that the combination of high blood glucose levels and VEGF overexpression exacerbates the vascular complications in the Akimba mouse eye [119,127].…”
Section: Transgenic Akimba Mouse Modelmentioning
confidence: 99%
“…The aforementioned vascular and inflammatory pathogenic pathways appear to be interlinked with neurodegeneration processes. In the Akimba mouse retinal thinning was observed and this was mainly associated to extensive degeneration of the photoreceptor layer and loss of retinal ganglion cells [119,124,128]. Finally, fibrosis pathogenic pathways can also be studied in the Akimba mouse model given that a substantial amount of fibrotic tissue was observed in the retinas of the majority of the old Akimba mice [119].…”
Section: Transgenic Akimba Mouse Modelmentioning
confidence: 99%